2006
DOI: 10.1002/anie.200601553
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Nanoflowers with Different Chemical Compositions and Physical Properties Grown by Limited Ligand Protection

Abstract: Colloidal nanocrystals with controlled size and shape play a key role in nanotechnology. [1][2][3] Organometallic [4][5][6] and related alternative (or so-called greener) [7][8][9][10] synthetic methods at elevated temperatures in non-aqueous solvents are the current mainstream strategies for producing high-quality nanocrystals. The ability to control the size and size distribution of nanodots using these strategies is reasonably well developed. Also, advances in the formation of 1D nanocrystals have recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
123
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(134 citation statements)
references
References 33 publications
9
123
2
Order By: Relevance
“…[12] Our and other groups have reported that zero-dimensional (0D) NPs spontaneously transformed into one-dimensional (1D), [13][14][15][16] two-dimensional (2D), [17] three-dimensional (3D), [18] or even more complex structures [19] due to a decrease of the stabilizer's surface density on the NPs. Likewise, metalic, [20] semiconductor, [21,22] and magnetic NPs [23] were found to transform from 0D spheres to 1D or 3D nanostructures during synthesis when the amount of stabilizer was gradually decreased. However, in comparison to chemical functionalities by different types of the stabilizers, the effect of the surface density of stabilizers is much less explored, and especially their roles on the shape alteration of NPs are not clearly known due to the absence of the quantitative analysis results.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Our and other groups have reported that zero-dimensional (0D) NPs spontaneously transformed into one-dimensional (1D), [13][14][15][16] two-dimensional (2D), [17] three-dimensional (3D), [18] or even more complex structures [19] due to a decrease of the stabilizer's surface density on the NPs. Likewise, metalic, [20] semiconductor, [21,22] and magnetic NPs [23] were found to transform from 0D spheres to 1D or 3D nanostructures during synthesis when the amount of stabilizer was gradually decreased. However, in comparison to chemical functionalities by different types of the stabilizers, the effect of the surface density of stabilizers is much less explored, and especially their roles on the shape alteration of NPs are not clearly known due to the absence of the quantitative analysis results.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that primary particles crystallographically align with adjacent ones can be understood as the result of oriented attachment and subsequent high-temperature sintering during synthesis. [6] Figure 2 b, c shows the secondary structures of CNCs of much larger size. The selected-area electron diffraction (SAED) pattern recorded on an isolated cluster about 174 nm in size reveals single-crystal-like diffraction (Figure 2 d).…”
mentioning
confidence: 98%
“…This trend is evidenced by a number of interesting works published in the past two years. [6][7][8][9][10] Manipulation of the secondary structures of nanocrystals is desired in order to combine the ability to harness the size-dependent properties of individual nanocrystals with the possibility to tune collective properties due to interactions between the subunits. Herein we report the synthesis of highly water dispersible magnetite (Fe 3 O 4 ) colloidal nanocrystal clusters (CNCs) with uniform size from about 30 to about 180 nm, each of which is composed of many single magnetite crystallites approximately 10 nm in size.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] This research trend has been evidenced by plenty of interesting works published in the past several years. [6][7][8][9][10][11] Manipulation of the secondary structures of nanocrystals leads to fine-tuned interactions between the submits and enhances the possibility to tune collective properties eventually. As one of the group II-VI semiconductors, ZnO has attracted increasing attention recently owing to its nontoxicity and chemical stability towards air, especially in its diverse optoelectronic applications.…”
Section: Introductionmentioning
confidence: 99%